Familial molar tissues due to mutations in the inflammatory gene, NALP7, have normal postzygotic DNA methylation - El Maarri, Osman (2006)
An imprinting disorder has been believed to underlie the etiology of familial biparental hydatidiform moles (HMs) based on the abnormal methylation or expression of imprinted genes in molar tissues. However, the extent of the epigenetic defect in these tissues and the developmental stage at which the disorder begins have been poorly defined. In this study, we assessed the extent of abnormal DNA methylation in two HMs caused by mutations in the recently identified 19q13.4 gene, NALP7. We demonstrate normal postzygotic DNA methylation patterns at major repetitive and long interspersed nuclear elements (LINEs), genes on the inactive X-chromosome, three-cancer related genes, and CpG rich regions surrounding the PEG3 differentially methylated region (DMR). Our data provide a comprehensive assessment of DNA methylation in familial molar tissues and indicate that abnormal DNA methylation in these tissues is restricted to imprinted DMRs. The known role of NALP7 in apoptosis and inflammation pinpoints previously unrecognized pathways that could directly or indirectly underlie the abnormal methylation of imprinted genes in molar tissues.